The Influence of Aluminum Tripolyphosphate on the Protective Behavior of an Acrylic Water-Based Paint Applied to Rusty Steels - Dongdong Song; Jin Gao; Lin Shen; Hongxia Wan; Xiaogang Li (Journal of Chemistry)
The protective performance, in conditions of total immersion, of an acrylic water-based paint applied to rusty steel, has been studied using electrochemical techniques. There was no rust, blister, crack, or flake that occurred on coating after 500 h immersion. The data obtained have enabled the protective mechanism to be proposed. The specific pigments utilized in the formulation of the paint studied can release phosphates to form a protective layer on metal substrate, which can impede the access of aggressive species to substrate surface. The coatings performed electrochemical activity in the beginning of immersion; then the layer formed and resistance of coating increased.